The Another look at the solution of the equations; the modified Benjamin-Bona-Mahony equation and the modified Korteweg-de Vries equation.: Otra mirada a la solución de las ecuaciones; la ecuación modificada de Benjamin-Bona-Mahony y la Korteweg-de Vries (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
In [1] the authors present an analytical method for solving nonlinear evolution equations, and apply it to find ”new solutions”, of the equations mBBM and mKdV. In this note we prove that these solutions can be found from the general solution and that the method exposed in [1], is not as effective as claimed.
Keywords: Korteweg-de Vries equation